1998
DOI: 10.1046/j.1365-2958.1998.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mycobacterial recA function: protein introns in the RecA of pathogenic mycobacteria do not affect competency for homologous recombination

Abstract: SummaryThe recA locus of pathogenic mycobacteria differs from that of non-pathogenic species in that it contains large intervening sequences termed protein introns or inteins that are excised by an unusual protein-splicing reaction. In addition, a high degree of illegitimate recombination has been observed in the pathogenic Mycobacterium tuberculosis complex. Homologous recombination is the main mechanism of integration of exogenous nucleic acids in M. smegmatis, a nonpathogenic mycobacterium species that carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
3
29
0
Order By: Relevance
“…Instead, M. canettii A was found to be able to successfully transfer DNA into the recipient M. canettii L despite predictions that M. canettii A-derived sequences only made up a minor part of other M. canettii genomes in in silico analyses (11). The impact of inteins on recombination in selected mycobacterial strains might thus be limited, in accordance with previous findings (40).…”
Section: Discussionsupporting
confidence: 78%
“…Instead, M. canettii A was found to be able to successfully transfer DNA into the recipient M. canettii L despite predictions that M. canettii A-derived sequences only made up a minor part of other M. canettii genomes in in silico analyses (11). The impact of inteins on recombination in selected mycobacterial strains might thus be limited, in accordance with previous findings (40).…”
Section: Discussionsupporting
confidence: 78%
“…1). These results indicated that the recA gene is present in all 36 of the species, a result probably related to the essentiality of RecA recombinase in mycobacteria, as suggested by Frischkorn and collaborators and Papavinasasundaram and collaborators (14,29). Moreover, the amplification yields were rather high, suggesting that the sensitivity of the PCR diagnosis would be quite good, even if the target sequences are present in single copy in the M. tuberculosis genome.…”
Section: Discussionsupporting
confidence: 52%
“…They can be found in proteins involved in DNA or RNA metabolism and biosynthesis (such as a ribonucleotide reductase in Anabaena [139]); cell division (such as an ATPase involved in chromatin remodeling in Deinococcus radiodurans [140]); transcription (such as the GyrA gyrase in mycobacteria [141]); and DNA replication (such as DnaX, the DNA polymerase subunit, in Synechocystis and the DnaB helicase in Rhodothermus marinus [142,143]), repair, and recombination (such as RecA in mycobacteria [144]). There are several nonexclusive hypotheses for their localization.…”
Section: Inteins Introns and Retroelementsmentioning
confidence: 99%